INTERCORRENCES WITH THE MISUSE OF TYPE A BOTULINUM TOXIN - Xavier da Rosa Bugni, Eliane; Giacomini , Alex (Health and Society, 2021)
Botulinum Toxin type A has become a great ally in aesthetic procedures because it is a very efficient non-surgical, aesthetic-therapeutic procedure. Known and much sought after for the result it provides in facial harmonization, by smoothing expression lines caused by repeated contractions carried out over the years, it has increased the demand for the technique, and with that, some complications and light, but transient complications arose. Thus, the objective of this article is to understand the process of application of botulinum toxin type A, its effects and complications (intercurrences) that may arise when not performing the technique as recommended, in addition to reviewing the literature and the protocol for applying the Botulinum toxin type A. The bibliographic research method, literature review of articles from the year 2000, in English and Portuguese, in search platforms of Scielo, Pubmed, Academic Google, atlas, dissertations and theses. Respecting the reapplication time is essential not only for complications, but also the patient's individuality, outlining a safe and effective path to avoid unwanted effects, thus ensuring a successful and attractive procedure both in the eyes of the professional and in the eyes of the clients .